Lessons learned on recruitment and retention in hard-to-reach families in a phase III randomised controlled trial of preparatory information for children undergoing general anaesthesia - C. Huntington; J. Timothy Newton; N. Donaldson; C. Liossi; P. A. Reynolds; R. Alharatani; M. T. Hosey (BMC, 2017)
Abstract Background Recruitment and retention are documented as two of the most difficult elements of conducting clinical trials. These issues are even more challenging in paediatric trials, particularly when the families being recruited and retained are deemed 'hard to reach'. Methods Through the authors' own reflection on the conduct of the trial this paper examines recruitment and retention with hard to reach families from the perspective of a recently completed clinical trial on preparatory information for children undergoing general anaesthesia for tooth extractions in which approximately 83% of those approached and eligible agreed to participate. Results The lessons learned for recruitment include: the importance of children's assent; maximising limited resources when screening and approaching potential participants; valuing families' time; and developing effective professional relationships. The retention rate was 83-85.5% at follow up time points up to 3.5 weeks following recruitment, insights into how this was accomplished include: ensuring continuity of care; determination to connect via telephone; valuing families' time; and close monitoring of appointment date changes. Conclusions Implications for future paediatric trials with hard to reach families are discussed. Trial registration ISRCTN18265148 ; NIHR Portfolio 10,006. Date of Registration: 29 November 2013. The trial was registered after commencement but before completion of data collection.